Inteligência Emocional e Burnout na Prática Profissional dos Assistentes Sociais ("Temas Sociais" Journal, 2024)
Emotional intelligence and burnout are concepts that have been studied individually and in relation to each other, but there are few studies relating them to social work. The aim of this study is to understand the importance of emotional intelligence in the professional practice of social workers and to relate it to levels of burnout. A mixed methodology was applied, and the sample was collected using the "snowball" method, obtaining a total of sixty-one participants by carrying out a questionnaire with open and closed answers using Google Forms with social workers from different areas. The results were analyzed using the IBM® SPSS® program, and although the correlations did not reveal statistically significant relationships, it was possible to conclude a negative correlation between emotional intelligence and burnout, reflecting that the lower the levels of emotional intelligence, the higher the levels of burnout. There was also a negative correlation between burnout and years of professional experience, showing that the more years of professional activity, the less likely it is to suffer from burnout. Finally, there was a positive correlation between emotional intelligence and years of professional experience, showing that the more years of professional practice, the higher the levels of emotional intelligence.
Keywords: Emotional intelligence, burnout, social work, professional practice; Emotional intelligence; Burnout; Social work; Professional practice